Results of a pilot feasibility randomised controlled trial exploring the use of an electronic patient-reported outcome measure in the management of UK patients with advanced chronic kidney disease. Issue 3 (18th March 2022) - Kyte, Derek; Anderson, Nicola; Bishop, Jon; Bissell, Andrew; Brettell, Elizabeth; Calvert, Melanie; Chadburn, Marie; Cockwell, Paul; Dutton, Mary; Eddington, Helen; Forster, Elliot; Hadley, Gabby; et al.
Abstract : Objectives: The use of routine remote follow-up of patients with chronic kidney disease (CKD) is increasing exponentially. It has been suggested that online electronic patient-reported outcome measures (ePROMs) could be used in parallel, to facilitate real-time symptom monitoring aimed at improving outcomes. We tested the feasibility of this approach in a pilot trial of ePROM symptom monitoring versus usual care in patients with advanced CKD not on dialysis. Design: A 12-month, parallel, pilot randomised controlled trial (RCT) and qualitative substudy. Setting and participants: Queen Elizabeth Hospital Birmingham, UK. Adult patients with advanced CKD (estimated glomerular filtration rate ≥6 and ≤15 mL/min/1.73 m 2, or a projected risk of progression to kidney failure within 2 years ≥20%). Intervention: Monthly online ePROM symptom reporting, including automated feedback of tailored self-management advice and triggered clinical notifications in the advent of severe symptoms. Real-time ePROM data were made available to the clinical team via the electronic medical record. Outcomes: Feasibility (recruitment and retention rates, and acceptability/adherence to the ePROM intervention). Health-related quality of life, clinical data (eg, measures of kidney function, kidney failure, hospitalisation, death) and healthcare utilisation. Results: 52 patients were randomised (31% of approached). Case report form returns were high (99.5%), as was retention (96%). Overall, 73% of expected ePROM questionnaires were received. Intervention adherence was high beyond 90 days (74%) and 180 days (65%); but dropped beyond 270 days (46%). Qualitative interviews supported proof of concept and intervention acceptability, but highlighted necessary changes aimed at enhancing overall functionality/scalability of the ePROM system. Limitations: Small sample size. Conclusions: This pilot trial demonstrates that patients are willing to be randomised to a trial assessing ePROM symptom monitoring. The intervention was considered acceptable; though measures to improve longer-term engagement are needed. A full-scale RCT is considered feasible. Trial registration number: ISRCTN12669006 and the UK NIHR Portfolio (CPMS ID: 36497).